01.14 Novel mechanism mediated by the IL23/TH17 axis contributing to auto-immune arthritis. (1st March 2017) - Pfeifle, René; Rothe, Tobias; Ipseiz, Natacha; Scherer, Hans U; Culemann, Stephan; Harre, Ulrike; Hueber, Axel J; Herrmann, Martin; Blüml, Stephan; Nimmerjahn, Falk; Schett, Georg; Krönke, Gerhard
Abstract : Background: Checkpoints and mechanisms regulating the onset of rheumatoid arthritis (RA) remain largely elusive. Apart from B cells and auto-antibodies, Th17 cells were shown to critically contribute to disease development. Mice lacking IL-23, a cytokine controlling the pathogenicity of Th17 cells, are completely protected against arthritis. Yet, the exact role of the IL-23/Th17 axis during this autoantibody-driven disease remain incompletely understood. Material and methods: IL23A -/- mice and mice receiving an IL23 blocking antibody were analysed during active and passive arthritis models including collagen-induced arthritis (CIA), the K/BxN arthritis model, collagen-antibody induced arthritis (CAIA) and K/BxN-serum transfer arthritis. Both clinical, histological and immunological parameters of arthritis were assessed. IgG glycosylation was analysed using the MALDI-TOF technique. IgG activity was determined by measuring the cytokine release of immune-complex-stimulated myeloid cells. To study the crosstalk between B cells and Th17 cells, co-culture experiments were performed. Results: Here we report, that the IL-23/Th17 axis did not directly contribute to auto-antibody induced inflammation within inflamed joints, but controlled the glycosylation profile and inflammatory activity of auto-antibodies during the prodromal phase of disease. Th17 cells were found to accumulate in germinal centres auf secondary lymphatic organs prior to onset of experimental arthritis, where they suppressed the expression of β-glactoside α2, 6-sialyltransferase 1 (St6gal1) in differentiating plasmablasts. The consecutive change in the immunoglobulin G (IgG) glycosylation profile provoked a shift towards a pro-inflammatory autoantibody repertoire and triggered the inflammatory phase of arthritis. Plasmablasts of RA patients similarly displayed a decreased St6gal1 activity, while IgG from these individuals showed corresponding changes in its glycosylation profile as well as an increased inflammatory activity, suggesting that related pathways might contribute to onset and progression of autoantibody-mediated diseases in humans. Conclusion: Our current findings identify a novel IL-23/Th17-dependent checkpoint that controls autoantibody activity, unmasks a preexisting breach in humoral tolerance, and initiates the transition from a stage of asymptomatic autoimmunity into inflammatory autoimmune disease.